Circulating tumor DNA – from biology to potential clinical applications in diffuse large B-cell lymphomas - Lewandowski, Krzysztof; Gwóźdź-Bąk, Kinga (Contemporary Oncology/Współczesna Onkologia, 2025)
During the last 20 years, significant progress has been made in understanding the biology of cancer cells. Assessment of the molecular profile of neoplastic cells collected by tissue biopsy using next-generation sequencing techniques makes it possible to diagnose the specific diffuse large B-cell lymphoma subtype and to personalize the therapy applied through the rational use of molecularly targeted drugs. Similar to the other methods of biopsy material evaluation, this method has some limitations. It may fail in cases when tissue biopsies do not fully capture intratumor genetic heterogeneity. For this reason, research has been undertaken to find new laboratory methods to study the genetic heterogeneity of cancer cells and to characterize all lymphoma cells at once, regardless of the origin of the tumor cells and the stage of its transformation. One promising diagnostic approach is the evaluation of total free circulating DNA, including circulating tumor DNA, using molecular biology techniques.